(untitled) - CAMPBELL, MARY (USA, 1992)
1.Starting with quattro pro for windows / 2.Basic Spreadsheet entries / 3.Chaging cell and page properties / 4.Rearranging cell entries / 5.Makinng cell entries with commands / 6.Printing your entries / 7.Files / 8.Fuctions / 9.Basic graphic features / 10.Advanced graphics / 11.Data management / 12.Customizing Quattro pro / 13.Automating Quattro pro tasks / 14.Advanced macro options
Incluye indice analitico pag.863
Keywords: PROGRAMAS PARA COMPUTADOR